Pengaruh Suhu dan Waktu Maserasi terhadap Karakteristik Ekstrak Daun Bidara (Ziziphus mauritiana L.) sebagai Sumber Saponin - Chairunnisa, Sarah; Wartini, Ni Made; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p07, 2019)
Bidara ( Ziziphus mauritiana L.) is one of the most natural ingredients that has the potential as a source of saponins. Saponins can be used as a natural surfactant which can replace the synthesis surfactant. The purpose s of this research were to determine the effect of temperature and time of maceration on the characteristics of bidara leaf extract (Ziziphus mauritiana L.) and to obtain the best maceration temperature and time in producing the bidara leaf extract (Ziziphus mauritiana L.) as a source of saponins. This research is using randomized block design with two factors. The first factor is the maceration temperature which consists of 3 levels, namely 29 ± 1°C , 40±2 ° C, and 50±2 ° C . The second factor is the maceration time which consists of 3 levels, namely 36 hours, 48 hours, and 60 hours. Each treatment is grouped into 2 based on the time of implementation so obtained 18 units. The results showed that treatment of temperature and maceration time and interaction between the treatment were had very significant on the yield, crude saponins levels, and the height of bidara leaf extract foam (Ziziphus mauritiana L.) as the source of saponins. Temperature of 50±2°C and maceration time of 48 hours is the best treatment to produce bidara leaf extract (Ziziphus mauritiana L.) as a source of saponin with a yield characteristic of 42.59±0.02%, crude saponin levels of 40.84±0.09% and foam height 29.03±0.38 mm . Keywords: Ziziphus mauritiana L., saponins, extraction, temperature, maceration time